Characterization of barley germplasm for leaf stripe (Pyrenophora graminea) resistance based on incidence and severity parameters - Arabi, M. I. E.; Jawhar, M.; Al-Shehadah, E. (Acta Biologica Szegediensis, 2020)
Barley leaf stripe (BLS) caused by Pyrenophora graminea is an important seed-borne disease of barley causing significant yield and quality losses worldwide. The development of resistant cultivars has proven difficult, therefore, in this work, BLSresistant barley germplasm was developed by crossing six barley cultivars currently used in Europe and West Asia. Out of 270 doubled haploid lines derived from these crosses, 40 lines were evaluated under field artificial infection conditions using incidence (I; proportion of diseased plants) and severity (S; proportion of infected leaf area per plant). Disease resistance parameters showed a broad range of variation in mean I and S values with a continuum of resistance levels ranging from highly susceptible to highly resistant with values being consistently higher in the susceptible ones. However, eight promising resistant lines with high yield per plant were identified. Moreover, BLS severity increased linearly as incidence increased (r = 0.76, P < 0.001). This work suggests that BLS resistance sources identified in this study can be used for further genetic analysis and introgression for varietal improvement, and that the positive correlation between I and S parameters may be beneficial for many types of studies on this disease.